Efektivitas bantuan UMKM dan strategi penguatan UMKM di Kota Magelang - Hutajulu, Dinar Melani; Islami, Fitrah Sari (Journal of Economics Research and Policy Studies, 2024)
The government provides assistance to maintain the resilience of MSMEs during Covid-19. The research aims to analyze the effectiveness of government assistance to MSMEs and determine appropriate strengthening strategies. The research was conducted in Magelang City, with the research object being 32 respondents receiving BPUM assistance in 2021. Data collection methods were carried out by observation, interviews, and filling out questionnaires. The analysis in this research includes descriptive analysis, one sample chi-square test analysis, Wilcoxon signed rank test analysis, and SWOT analysis. The results show different opportunities for each micro-enterprise to get BPUM assistance based on length of business, type of business, and type of product. Another finding is that BPUM assistance is effective in increasing micro businesses in capital, production, and added value but ineffective in increasing the workforce. Strengthening strategies such as unique products, partner relationships, digital marketing, promotions, improving the quality of human resources, innovation, and exploiting tourism potential are the right strategies to implement.